Women's empowerment, children's nutritional status, and the mediating role of household headship structure: Evidence from sub‐Saharan Africa - Aaron K. Christian; D. Yaw Atiglo; Michael A. Okyere; Akua Obeng‐Dwamena; Grace S. Marquis; Andrew D. Jones (Maternal and Child Nutrition, 2023)
Abstract We aimed to examine the association between women's empowerment and childhood nutritional status while accounting for the mediating role of household headship structure. Cross‐country, cross‐sectional quantitative data from the most recent Demographic and Health Surveys (2015–2018) were used. Women's empowerment was measured as a composite index of participation in household decision‐making, attitude towards domestic violence, and asset ownership. Childhood nutrition status was measure as anaemia (haemoglobin concentration < 110g/L), stunting (height‐for‐age z‐scorescore <−2) and the co‐occurrence of anaemia and stunting. Applying the Lewbel two‐stage least squares, women's migration status was used as an instrumental variable. We used data on 25,665 woman‐child dyads from eight sub‐Saharan African countries: Burundi (2016), Ethiopia (2016), Guinea (2018), Malawi (2016), Mali (2018), Zimbabwe (2015), Uganda (2016), and Tanzania (2015). The women were in their reproductive ages (15–49 years) and children were under 5 years old. The findings showed that an increase in women's empowerment index reduces children's likelihood of being anaemic and having a co‐occurrence of anaemia and stunting [coeff (SE), −0.114 (0.025) and −0.072 (0.032), respectively]. Specifically, an increase in asset ownership or decision‐making dimensions of empowerment significantly reduces the likelihood of anaemia and the co‐occurrence of anaemia and stunting among children. Children of empowered women from male‐headed households were more likely to be anaemic and be concurrently anaemic and stunted compared to their counterparts whose mothers were from female‐headed households. Interventions designed to improve childhood nutrition through women's empowerment approaches need to consider asset ownership and instrumental agency of women while acknowledging the mediating effect of household headship typology.